Trypanosoma cruzi DTU II coinfection with bacteria producing prolonged cutaneous lesion in a healthy young male - Rangel-Gamboa, Lucia (2023)
Chagas disease (CD) is a neglected tropical disease caused by Trypanosoma cruzi and is genetically classified in six discrete typing units (DTUs). The isolates reported in Mexico are generally associated with DTU I. We presented a case of a prolonged cutaneous lesion in a Mexican man, caused by DTU II in coinfection with Bacillus velezensis and Corynebacterium sp. The patient assessment included a complete clinical history, physical exam, laboratory tests, and a skin biopsy. In the facial tissues, intracellular parasites were revealed. The PCR tests were positive for T. cruzi in tissue and blood samples. DNA satellite sequencing was correlated with the DTU II. The initial serological tests reported negative results. However, four months later, two serological tests reported positive results. These exams were performed in different health centers. Mexico is considered an endemic area for CD; nevertheless, this is just the second cutaneous case associated with a DTU different from DTU-I noted in this country. From an ecological point of view, this fact suggests a geographical expansion of DTU II and an association with atypical skin manifestations. Further studies should be conducted to understand this exciting association between DTU-II and prolonged cutaneous expression in humans.